Character loaded big books for young learners of English - Dian Febrianti (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2019)
This research is made to produce big books that are intended to teach English, and to build character. This product is addressed for the  beginner of Englishlanguage learners.. The methods used by this research is Research Development. The instrument used is questionnaire, which generates data in form of quantitative and qualitative. The result of this research is books with five different titles. Each of the titles teaches one of the five primary characters. The quality of the product is very high. Therefore, it is decent to be implemented as a learning media.  DOI: 10.26905/enjourme.v2i2.3561